Evaluating the level of trace elements in Iraqi women with early-stage breast cancer: Evaluating the level of trace elements - Shahad A. Jarallah; Falah S. Al-Fartusie; Dheaa Sh. Zgeer (Iraqi Journal of Cancer and Medical Genetics, 2024)
Breast cancer is one of a group of diseases in which cells in the breast tissue change and divide uncontrollably, causing these cells to clump. Invasive cancers can spread to nearby lymph nodes or other organs (metastasize). Elements are found in different forms in nature, and these elements are very necessary for the performance of the body›s various functions; Elements such as iron and zinc are essential components of enzymes where they attract or subtract molecules and facilitate their conversion to specific end products. Few elements donate or accept electrons during redox reactions. This study aimed to follow the change in the level of trace elements (TEs) and the extent to which these changes are related to the risk of breast cancer before taking chemotherapy or removing the tumor, by drawing 5 ml of venous blood from 120 women (60 patients and 60 control), the serum was separated then used to measure Zn, Cu, Fe, Mg, Cr, and whole blood (2ml) to measure Pb, Cd. In addition to studying the receiver operating characteristic curve (ROC) of these elements. Evaluation of trace elements revealed a significant increase in the levels of Fe, Cu, Pb, and Cd, in contrast to a significant decrease in the levels of Zn and Mg in breast cancer patients compared to a healthy control group.